Meta-Analysis: Effects of Exclusive Breastfeeding, Antenatal Care Visit, and Maternal Education on Stunting in Toddlers - Tari, Putri Inrian; Rahardjo, Setyo Sri; Setiyadi, Noor Alis (Journal of Maternal and Child Health, 2023)
Background: Stunting is a condition in which toddlers have less height according to their age. WHO reports that there are around 149.2 million toddlers experiencing stunting worldwide. This study aims to analyze and estimate the magnitude of the effect of exclusive breastfeeding, antenatal care visits, and maternal education level on the incidence of stunting among toddlers based on the results of similar previous studies. Subjects and Method: This study is a systematic review and meta-analysis using the PRISMA flow chart and the PICO model. Population: toddlers. Intervention: exclusive breastfeeding, the mother often visits antenatal care, and high maternal education. Comparison: not exclusive breastfeeding, mothers rarely visit antenatal care, and low maternal education. Outcome: stunting. The databases used were Google Scholar, PubMed, ScienceDirect, Elsevier, Scopus, SpringerLink, BioMed Central, PLOS ONE, and Emerald with the keywords (“Exclusive Breastfeeding” OR “Antenatal Care” OR “Mother's Education”) AND “Stunting” AND “Children” AND “aOR”. There were 15 cross-sectional studies published in 2013-2023 that met the inclusion criteria. Analysis data were RevMan 5.3. Results: A meta-analysis of 15 articles with a cross-sectional study design was carried out from Ethiopia, India, Tanzania, Rwanda, Pakistan and Indonesia in under-fives with a sample size of 285,221. The results of the meta-analysis showed that toddlers who were exclusively breastfed experienced stunting by 0.54 times compared to toddlers who were not exclusively breastfed (aOR= 0.54; 95% CI= 0.35 to 0.85; p<0.001), toddlers born to mothers who had frequent antenatal visits care experienced stunting by 0.81 times compared to toddlers born to mothers who rarely visited antenatal care (aOR= 0.81; 95% CI= 0.72 to 0.90; p= 0.001), and toddlers born to mothers with higher education experienced stunting by 0.72 times compared to toddlers born to mothers with low education (aOR= 0.72; 95% CI=0.61 to 0.86; p=0.003). Conclusion: Toddlers who get exclusive breastfeeding, mothers who often visit antenatal care, and a high level of maternal education can reduce the risk of stunting in toddlers. Keywords: Exclusive breastfeeding, antenatal care, maternal education, stunting. Correspondence:Putri Inrian Tari. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: putriindriantari@gmail.com. Mobile: +6282282432594